The Role of The Community and The Efforts to Preserve The Potential of Cultural Heritage of The Rawa Bayu Tourism - Alfian Nur Muzaki; Iwan Alim Saputra; Aziz Budianta (Media Wisata, 2022)
Rawa Bayu is a water tourism area and religion can be felt as well as the indigenous people around the tourism area and the immigrants who visit the place who have all the necessities related to the benefit of humans, namely as a support for learning materials at the high school or MA level as well as at the lecture level. The purpose of this study was to determine the collaborative management of the surrounding community with the Banyuwangi Regency Tourism Office and how big the role of the surrounding community in maintaining and preserving several vital objects of cultural heritage in the Rawa Bayu tourism area. The use of the method is to use a qualitative approach by observing directly and documenting activities. Authors use literature studies to support a more definite understanding that comes from valid data. The data analysis technique used componential and descriptive analysis. The results of the study include an overview of the study area, the potential for the existence of ecotourism, and the role of the community in preserving historical objects around the ecotourism area.